Academic Engagement in students of Secondary and Bachelor Education: towards a complete understanding of the term - Marta Oporto Alonso; Marina Fernández; Salud Porras (Ignatianum University Press, 2019)
The academic engagement is defining with three dimensions: vigour (high degree of vitality and effort in undertaken tasks), dedication (enthusiasm, inspiration and elaboration of goals and challenges at work) and absorption (concentration and compliance of tasks) (Manzano, 2004; Salanova et al., 2000). The objectives of this theorical revision are: offer a brief exposition of the origins and the definition of the concept of academic engagement, describe some of the manifestations of academic engagement in different school stages (from secondary education to bachelor education) and suggest some direct implications of the term in the work of the educator.